2015
DOI: 10.1186/s13568-015-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of an alkaline-based chemical treatment for the purification of polyhydroxybutyrate produced by a mixed enriched culture

Abstract: This study focused on investigating the feasibility of purifying polyhydroxybutyrate (PHB) from mixed culture biomass by alkaline-based chemical treatment. The PHB-containing biomass was enriched on acetate under non-sterile conditions. Alkaline treatment (0.2 M NaOH) together with surfactant SDS (0.2 w/v% SDS) could reach 99% purity, with more than 90% recovery. The lost PHB could be mostly attributed to PHB hydrolysis during the alkaline treatment. PHB hydrolysis could be moderated by increasing the crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 52 publications
(65 reference statements)
5
32
0
1
Order By: Relevance
“…Previous studies on alkali extraction have reported up to 96% PHA purity by using NaOH, and up to 99% when combined with SDS . When applied to the crude PHA from the present study, these methods led to 72% and 76% purity, respectively (Table ), giving further indication of the recalcitrance of the mixed microbial culture used for the PHA production.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Previous studies on alkali extraction have reported up to 96% PHA purity by using NaOH, and up to 99% when combined with SDS . When applied to the crude PHA from the present study, these methods led to 72% and 76% purity, respectively (Table ), giving further indication of the recalcitrance of the mixed microbial culture used for the PHA production.…”
Section: Resultssupporting
confidence: 61%
“…Sodium hydroxide digestion, as well as combined NaOH and SDS digestion, were performed according to the protocols suggested by Jiang et al . Incubations were done using 100 mg of crude PHA and 4 mL of digestion solution, containing NaOH 0.2 mol/L or NaOH 0.2 mol/L with SDS 0.2% ( w / v ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…glucose, methanol or acetic acid, contribute significantly to 48 the overall environmental impacts of the process, (Patel et al, 2005). 49 In order to address these issues on higher production costs and environmental impacts, a 50 microbial community engineering process for PHA production has been proposed, as an of the PHB is comparable to that of a commercial polymer (Jiang et al, 2015).…”
mentioning
confidence: 99%
“…Por se tratar de um produto intracelular, o P(3HB) deve ser extraído da célula ao término do cultivo e estima-se que o impacto do custo de extração deste biopolímero, no custo total do processo de produção, possa representar mais de 50% do valor final do produto [4] . Os métodos utilizados no processo de extração de P(3HB) são: extração por solventes orgânicos como clorofórmio [5] ; carbonato de propileno [6,7] ; e dicloroetano [8] ; digestão enzimática [9,10] ; métodos mecânicos [11,12] e o uso de soluções aquosas de surfactantes e quelantes [13,14] . Dentre estes, os que fazem uso de solventes são os mais extensivamente utilizados.…”
Section: Introducãounclassified